Gamifikasi dan Teknologi Komunikasi : Meningkatkan Keterlibatan dan Interaksi Berkomunikasi dalam Pendidikan - Arsana, I Nyoman Alit; Merliana, Ni Putu Eka; Purnawati, Ni Wayan (Dharma Duta, 2024)
Communication technology with gamification is an innovative strategy that can change behavior in the learning process, especially in student engagement and interaction. In the context of learning, communication technology, such as e-learning, is used to connect students and teachers through digital platforms that provide learning content, discussion forums, and assignments. Communication technology with gamification provides opportunities for students to interact widely in the learning process. This study aims to explore the strategies used in the utilization of communication technology with game elements in gamification so as to produce positive behavior in communication engagement and interaction between students, students, teachers, and students with content. The method used was a literature review with the research spanning from 2014 to 2024. The results of this study show a conceptual model that can be used to develop learning strategies for gamification. The results will provide practical insights into developing an engaging and fun communication technology-based learning model to increase communication engagement and interaction.